2021
DOI: 10.1016/j.ijid.2021.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, outcomes and factors associated with mortality: A prospective study from three COVID-19 referral care centres in West Africa

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 25 publications
4
29
1
Order By: Relevance
“…For example, on the site of Johns Hopkins University dedicated to COVID-19 [ 1 ], data clearly shows this influence on the case fatality rate corresponding to the cumulative deaths recorded 5 months after the beginning of the outbreak (12 May 2020) vs. the median age of many countries in 2017 ( Figure 1 ). This first observation has been confirmed by many studies in different countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] such as in France ( Figure 2 ), and we will confirm in this paper that the age of the patients suffering from COVID-19 is a good predictor of severity.…”
Section: Introductionsupporting
confidence: 85%
“…For example, on the site of Johns Hopkins University dedicated to COVID-19 [ 1 ], data clearly shows this influence on the case fatality rate corresponding to the cumulative deaths recorded 5 months after the beginning of the outbreak (12 May 2020) vs. the median age of many countries in 2017 ( Figure 1 ). This first observation has been confirmed by many studies in different countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] such as in France ( Figure 2 ), and we will confirm in this paper that the age of the patients suffering from COVID-19 is a good predictor of severity.…”
Section: Introductionsupporting
confidence: 85%
“…Four studies found preexisting CVD was associated with higher COVID-19 mortality, including 2 high-quality studies using databases from South Africa to pool together large samples. 10,11,31,32…”
Section: Resultsmentioning
confidence: 99%
“…10 Lastly, the study pooling data from Burkina Faso and Guinea found hypertension was associated with death from COVID-19 infection (aOR, 2.1 [95% CI, 1.2–3.4]). 11…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies on predictors of mortality in COVID-19 patients have been undertaken in Africa, with mixed results regarding the role of diabetes as a comorbidity in death. Diabetes has been demonstrated to be a predictor of mortality in some studies [12][13][14], although this idea has not been supported in others [15][16][17][18]. Varied study designs and populations provide different estimates and impact sizes in these published publications.…”
Section: Introductionmentioning
confidence: 98%